Relational leadership in education a phenomenon of inquiry and practice - Giles, David L. (Routledge, Taylor & Francis Group, 2019)
"Relational Leadership in Education considers 'relational leadership' within the context of education, critiquing the current ideological 'context' and contemporary understandings of its influence. Employing a phenomenological approach, this book explores the relational nature of education, relational leadership, and the organisational culture to provide a more sophisticated exploration of practice-based wisdom. It offers an extensive range of activities for further thinking on the experiential nature of relational leadership, grouped around a number of themes"--